Trade and factor-market effects of New Zealand's reforms. Report to the Foundation for Research Science and Technology - Alan Deardorff; Ralph Lattimore (New Zealand Institute of Economic Research (NZIER), 1999)
International trade protectionism is frequently supported on the assumption that importables provide more jobs for unskilled labour than does the exportable sector. This contention is questioned here by reference to the factor intensity of New Zealand trade. Exportables are found to be more intensive in the use of unqualified labour services, especially females. The paper examines these issues before and after the recent reforms with their associated trade changes and analyses these effects on the sectoral employment of labour, capital and land.
Keywords: 330; Wirtschaftsreform; Faktorintensität; Beschäftigungseffekt; Außenhandelswirtschaft; Protektionismus; Neuseeland